Sample path properties of fractional Riesz–Bessel field of variable order - Lim, S. C.; Teo, L. P. (AMER INST PHYSICS, 2008)
In this paper we consider fractional Riesz-Bessel field of variable order, which is also known as multifractional Riesz-Bessel field. Sample path properties of this random field such as local regularity, locally self-similar property, Hausdorff dimension of the graph, and long/short range dependent property are studied. The relationship between the multifractional Riesz-Bessel field and the multifractional Brownian field is also established. (c) 2008 American Institute of Physics.